Political communication as an informational aspect of interaction between policy subjects - A. K. Botasheva (Современная наука и инновации)
The article examines political communication and shows that the main institution of the political system is the state, which initially needs a policy that unites the citizens of this state. The article analyzes politics as a mechanism for organizing society's life, which is impossible without political communication. A large place in the work is occupied by the consideration of the tasks of political communication, among which the main task remains to ensure the dissemination of the very information without which the functioning of the state is impossible. It is concluded that political communication is a kind of mechanism by which power is realized in society.